Violence, Nonviolence, and the Effects of International Human Rights Law. Issue 2 (6th February 2019) - Lupu, Yonatan; Wallace, Geoffrey P. R.
Abstract: Under what conditions are individuals more likely to approve of human rights abuses by their governments? While various theoretical expectations have been offered about public approval of repression, many of them have not been directly tested. We analyze the effects of differing opposition tactics, differing government tactics, and legal constraints on approval of repression through a series of survey experiments in India, Israel, and Argentina. Our results indicate that violent action by opposition groups consistently increases support for government repression. In the context of contentious politics, we find that the effects of international law vary by national context. While our respondents in India were less likely to approve of their government when told the government violated international law, the same information likely increased approval of the government in our Israel experiment. The findings provide insights into the microfoundations of existing theories and suggest areas for theory refinement.